Correlation of Processing Techniques with Some Quality Indexes of Soy-Akamu Prepared with Yellow Maize, Sprouted and Un-Sprouted Soybean - Chikodili Ugochukwu; Innocent Nwazulu Okwunodulu; Joel Ndife; Stella Ubbor (Indonesian Food and Nutrition Progress, 2022)
Akamu or ogi is a commonly relished gruel when prepared with hot water by the sick, recovering patients and infants in Nigeria. It is nutritionally deficient due to inevitable processing losses which called for fortification with soybean (soy-akamu or soy-ogi). Soy-akanu was prepared from steeped yellow maize, sprouted and un-sprouted soybean cotyledons using different processing techniques. Proximate, micronutrients and functional properties were evaluated with standard analytical methods. The results showed that proximate composition of soy-akamu produced from dried teeped maize and sprouted soybean cotyledons had higher protein (63.20%), fibre (0.33%), ash (1.11%), energy (384.28 Kcal) and least moisture content (4.53%). The paste samples had respective values of 0.77, 3.06%; 0.00, 0.00%; 0.71, 1.02%; 29.86, 3303%; 143.50, 145.37 mg/100g, and 64 and 36-64-76%. Dried soy-akamu also had the highest calcium (41.18, iron (0.99), phosphorous (0.27), zinc (48.02), potassium (0.45), vitamin C (24.60) and least in magnesium (0.07 mg/100g) content. The paste samples had respective values of 40.13, 41.14; 0.86, 0.92; 0.39, 0.41; 0.39, 0.41; 20.46, 23.65 mg/100g with respective magnesium (0.10-0.12)  and phosphorous ( 0.25, 2.21 mg/100g) contents. Different processing techniques had significant (p<0.05) variations in proximate, micronutrient and functional properties of the soy-akamu and also their major sources of nutrient losses.